2022
DOI: 10.1002/jsfa.11816
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis revealed accumulation‐assimilation of selenium and physio‐biochemical changes in alfalfa (Medicago sativa L.) leaves

Abstract: BACKGROUND Selenium (Se) is an increasing concern for investigators predominantly because of its consumption in the human body mainly from crops. As the fourth largest plant crop globally, alfalfa is one of the most important forages. Alfalfa was fertilized with selenium(IV) (Se(IV)) under field conditions to study the accumulation and assimilation of Se(IV) and to assess the impact of Se fertilization. RESULTS It was analyzed that the physio‐biochemistry, Se species, combined with transcriptome after spraying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The RNA-Seq method has been used to analyze DEGs and has become a standard in multiple research fields ( Costa-Silva et al., 2023 ). RNA-Seq technology can be used to identify genes related to Se transportation, accumulation, and assimilation ( Hu et al., 2022 ). The transport mechanism of Na 2 SeO 3 is more complex than that of Na 2 SeO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The RNA-Seq method has been used to analyze DEGs and has become a standard in multiple research fields ( Costa-Silva et al., 2023 ). RNA-Seq technology can be used to identify genes related to Se transportation, accumulation, and assimilation ( Hu et al., 2022 ). The transport mechanism of Na 2 SeO 3 is more complex than that of Na 2 SeO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the adverse health effects of insufficient dietary Se, several food items have been enriched with Se. Additionally, it is suggested that the biofortification of crops like alfalfa can be achieved by supplementing Se through fertilizers ( Hu et al., 2022 ). There are currently very few preliminary studies on Se enrichment in alfalfa, with the majority of research focusing on the kinetics of selenium uptake in multiple-harvested hay ( Kovács et al., 2021 ), the impact of Se on quality and yield ( Hu et al., 2010 ), and the effect of animal husbandry after feeding Se-enriched alfalfa ( Pan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hay production and plant height were calculated using the approach described in Hu et al (2010). The Se accumulation was computed using the method of Hu et al by multiplying the hay yield and the Se content of alfalfa harvested during the initial flowering period (Hu et al, 2010).…”
Section: Determination Of Se Content and Agronomic Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Se as a trace element, can participate in the formation of enzymes that protect plant cells from oxidation, biotic and abiotic stresses, and play a beneficial role in plant growth. Se can also be added to the soil as a fertilizer to improve the yield and quality of crops [ [21] , [22] , [23] ]. Bocchini et al studied the increased resistance of maize to drought stress by inducing drought tolerance under exogenous Se supply [ 24 ].…”
Section: Introductionmentioning
confidence: 99%